Tanggungjawab Sosial Perusahaan Bank Syari'ah (Studi Kasus pada Bank Muamalat Indonesia Cabang Malang) - Ludigdo, Unti; Dhanias, Fitriana Rakhma (Universitas Brawijaya, Indonesia, 2011)
The objective of this study is to explore and describe motives and form of social responsibility in the Islamic bank. The qualitative method is used in study. Based on case study in a branch of Bank Muamalat Indonesia (BMI) in Malang, researchers can find the meaning of social responsibility. Informants show that the social responsibility activities are based on metaphor of religious motivation, such as doing function as a khalifatullah fil ardh and to maintain hablumminannas and hablumminallah in their life. So, the implementation of social responsibility in Islamic bank is not only based on accountability in the economy, social, and environment context, but also accountabity to God. The implication of this meaning, social responsibility activities are done by giving and distributing zakat, infaq, shadaqah (ZIS), doing Aksi Tanggap Muamalat (ATM) when is happened a disaster, and then forming Komunitas Usaha Mikro Muamalat Berbasis Masjid (KUM3). All of programs are organized by Baitul Mal Muamalat (BMM), the social institution of BMI.